Effects of YuPingFeng granules on acute exacerbations of COPD: a randomized, placebo-controlled study - Ma JF; Zheng JP; Zhong NS; Bai CX; Wang HY; Du J; Li FL; Chen YW; Shi Z; Li X; Chen PY (International Journal of COPD, 2018)
Jinfang Ma,1 Jinping Zheng,1 Nanshan Zhong,1 Chunxue Bai,2 Haoyan Wang,3 Juan Du,4 Fenglei Li,5 Yanwei Chen,6 Zhe Shi,7 Xin Li,8 Pingyan Chen9 1State Key Laboratory of Respiratory Disease, National Clinical Research Center for Respiratory Disease, Guangzhou Institute of Respiratory Health, the First Affiliated Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of China; 2Department of Respiratory Medicine, Zhongshan Hospital Affiliated to Fudan University, Shanghai, People’s Republic of China; 3Department of Respiratory Medicine, Beijing Friendship Hospital Affiliated to Capital Medical University, Beijing, People’s Republic of China; 4Department of Respiratory Medicine, The Affiliated Hospital of Guizhou Medical University, Guiyang, People’s Republic of China; 5Department of Respiratory Medicine, The Liwan Hospital of the Third Affiliated Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of China; 6Department of Respiratory Medicine, Nanshan People’s Hospital, Shenzhen, People’s Republic of China; 7Department of Respiratory Medicine, The First People’s Hospital, Huizhou, People’s Republic of China; 8Department of Respiratory Medicine, China Resource and Wisco General Hospital, Wuhan, People’s Republic of China; 9Department of Biostatistics, Southern Medical University, Guangzhou, People’s Republic of China Purpose: Recurrence of acute exacerbations has a major impact on patients with COPD. Therefore, effective prevention and treatment of exacerbation is crucial in the management of COPD, especially for patients with moderate to severe disease. This study evaluated the effectiveness of YuPingFeng granule administration in preventing exacerbation and improving symptom score, as well as its long-term (1 year) safety profile, in patients with COPD. Patients and methods: This was a randomized, double-blind, parallel, placebo-controlled study of 240 patients from eight centers in China. Participants were eligible if they had mild to severe COPD as defined by Global Initiative for Chronic Obstructive Lung Disease, had a history of at least two COPD exacerbations or one hospitalization within the previous year, and had remained clinically stable for over 4 weeks before the study. They were randomly assigned to receive 5 g of YuPingFeng or placebo, three times per day, for 1 year. The primary end point was the exacerbation rate over 1 year, and the analysis was by intention to treat. Secondary end points included symptom score, which was assessed by COPD assessment test (CAT) score and safety profiles. This trial was registered in the Chinese Clinical Trial Registry (http://www.chictr.org.cn; registration number: ChiCTR-IPR-15007023). Results: The YuPingFeng group had a significantly lower exacerbation rate than the placebo group (1.15 vs 1.55; risk ratio=0.677 [95% CI 0.531–0.863]; P=0.002) and a significantly reduced risk of second exacerbation (95% CI 0.326–0.772; P=0.002). After treatment, the mean change in the CAT score in the YuPingFeng group (-4.41±7.01) differed significantly from that in the placebo group (-2.49±5.31; P=0.001). YuPingFeng was well tolerated. Conclusion: YuPingFeng granules can be considered as a treatment option for COPD; this treatment prevents acute exacerbations of COPD and has a good safety profile. Keywords: COPD, exacerbation, treatment, YuPingFeng